System Reform: The Ever-Elusive Quest-An Australian Study of How System Middle Leaders' Role Enactment Influences the Attainment of Policy Coherence - Tania Leach (MDPI AG, 2024)
Within an educational context, the current aim of policy translation is to achieve policy coherence by strategically and structurally aligning components, enabling whole system reform. While acknowledging the importance of this coherence conceptualisation, the current literature perspective primarily emphasises message conveyance, and lacks a dimension that identifies policy coherence as the result of how individuals, including middle leaders, interpret and translate policy into actions, both individually and collectively. System middle leaders occupy a unique position within organisational structures, as they bridge the gap between executive system leaders and school- based leaders. To investigate how policy is interpreted and translated within their roles and the impact this has on attaining policy coherence, this study employed an interpretivist approach to exploratory case study methodology, grounded in a review of authoritative literature. The aim was twofold; first, to enhance understanding of policy coherence development at the system middle level by exploring the role enactment of system middle leaders within a large Australian government education system; and second, to examine the interconnectedness and impact of leaders' role enactment on policy coherence for system reform. Findings suggest that achieving policy coherence is hindered by a lack of role clarity among system leaders, in relation to policy implementation, stemming from the inconsistent interpretation and translation of policy into system strategy documentation and a deficiency in formal policy interpretation and role induction practices. As a result, individual system leaders often turn to informal policy interpretations and interactions with peers to clarify roles, leading to role tensions, accountability ambiguity and partial policy implementation. As a result, this study concludes that the integration of role theory, policy implementation theory and organisational alignment theory offers an interpretivist insight into the development of policy coherence for system reform, illuminating a theoretical pathway and practical recommendations for systems to attain policy coherence.